Tax systems and tax harmonisation in the East African Community (EAC): Report for the EAC/GTZ program 'Support to the EAC integration process' - Hans-Georg Petersen (Universität Potsdam, Lehrstuhl Finanzwissenschaft, 2010)
In the first part of the report of the GTZ expert group an overview on the basics of integration and tax harmonisation within a common market is given. Chapter II. concentrates on the problems of national and international tax law regarding double taxation before the harmonisation process within the EU is described in detail. This process is not a best practice example but at least the experiences made in the course of the last five decades are interesting enough and might contribute important information for regions, which more or less recently have started a similar endeavour. The harmonisation needs are discussed for value added taxation (VAT), excise taxation, and income taxation. The problems of tax administrations, procedures laws, taxpayers' rights and obligations as well as tax compliance are also taken into consideration. The second part of the study reviews the national tax systems within the EAC member countries. Before the single taxes are described in more detail, the macroeconomic situation is illuminated by some basic figures and the current stand of the inner-community integration analysed. Then the single tax bases and tax rates are confronted to shed some light on the necessities for the development of a common market within the near future. Again the value added tax laws, excise taxes and income taxes are discussed in detail, while regarding the latter the focus is on company taxation. For a better systematic analysis the national tax laws are confronted within an overview. The chapter is closed with a summary of the tax rates applied and a rough estimation of the tax burdens within the Partner States. The third part of this report contains the policy recommendations of the expert group following the same structures as the chapters before and presenting the results for the VAT, the excises and the corporate income tax (CIT). Additionally the requirements for tax procedures and administration as well as problems of transparency and information exchange are discussed in detail before the strategic recommendations are derived in close relation to the experiences made within the EU harmonisation process. The recommendations are based on the following normative arguments: (1) Tax harmonisation is a basic requirement for economic integration. (2) Equality of taxation is an imperative of tax justice and demands the avoidance of double taxation as well as the combat of tax evasion and corruption. (3) The avoidance of harmful tax competition between the Partner States. (4) The strengthening of taxpayers' rights in tax procedures. Hence, all kinds of income, goods and services should be taxed once and only once.
urn:nbn:de:kobv:517-opus-44693
Keywords: H2; H7; H83; F5; F15; N47; O2; 330; Centralization; decentralization; ethnic differences; fiscal federalism; fiscal planning; good governance; harmonization; integration; nation building; revenue sharing; sustainable fiscal policy; tax reform; Compliance; corruption; direct taxes; double taxation; East African Community; indirect taxes; information exchange; integration; international tax law; revenue authorities; tax administration; taxation; tax harmonization; tax system; transparency; Steuersystem; Steuerharmonisierung; Doppelbesteuerung; Handelsregionalismus; Ostafrika